Design and Sensitivity Analysis of Direct Conversion RF Receiver for IEEE 802.11a WLAN System at 5.8 GHz Frequency - Othman , A.R; Abd Aziz , A. A; Pongot. , K; Shairi , N. A; Mohd Nor, M.N (2012)
This paper presents the design of a direct conversion RF receiver and its sensitivity performance analysis for WLAN point to point communication at 5.8 GHz band based on IEEE 802.11a standard. The direct conversion RF receiver has been designed with proper selection of RF sub-components such as low noise amplifier (LNA), RF amplifier, power divider and filter. The selected RF sub-components of the RF receiver have been further analyzed for sensitivity performance in simulation. It is shown that the system noise figure influences RF receiver’s sensitivity. It is contributed by the first stage of RF subcomponent which is LNA in the RF front-end system. As results, the 1.31 dB system noise figure has been selected in order to get the best sensitivity for direct conversion RF receiver which is -74 dBm and dynamic range of 47 dB at 54 Mbps. Besides, this direct conversion RF receiver has met sensitivity specification for all data rates based on the IEEE 802.11a standard.